ARCHITECTURAL ACCULTURATION IN THE RESIDENCE OF BUDHI SANTOSO - Fransnino, Yenny Gunawan (Riset Arsitektur (RISA), 2017)
Abstract - In the Colonial Era, Dutch architects came to Indonesia and designed buildings based on their European expertise. They adapted to the factor of the tropical climate and indigenous cultural elements as a source of developing the process of architectural acculturation. The residence of Budhi Santoso in Yogyakarta is one of the products resulting from the acculturation between Dutch colonial architecture and the local wisdom and skills of Javanese culture. Architectural acculturation is an important topic that requires further study to contribute to the wealth of cultural knowledge, academic vocabulary as well as the variety of Indonesian architectural styles.The research method consists of qualitative research while the data processing has been obtained from studying the relevant background literature, direct observation, taking measurements, recording data in the shape of photographs and conducting interviews with the owner, Mr Budhi Santoso himself. The data were subjected to analysis using the comparative method by way of a comparison between Dutch and Javanese architecture. This analysis employs a theory derived from the study of background literature, namely Francis D.K. Ching’s theory concerning form, space and order to draw conclusions from the research study of cultural acculturation as observed in this residence.The conclusion indicates that Budhi Santoso’s residence is the product of a form of cultural acculturation between Dutch and Javanese architecture viewed from various angles, including the aspects of site/location, mass form, spatial order (lay-out), the elements of structural and non-structural scope and ornaments. These aspects have been affected by certain dominant features from one of the architectural styles, or else they have received the impact from a mixture between the two styles mentioned, leading to a new type of hybrid architecture. Keywords: Acculturation, Dutch Architecture, Javanese Architecture